A tricky singular papular peri‐cicatricial mammarian lesion - Carmen Cantisani; Federica Trovato; Luca Gargano; Antonio Di Guardo; Alexandru Bâja Vasile; Emanuele Rovaldi; Giulia Azzella; Iolanda Speranza; Giuseppe Soda; Michela Roberto; Tiziana Lettera; Giovanni Pellacani (Wiley, 2024)
Abstract Breast cancer represents the most common malignancy in women worldwide. In most cases, metastasis is the leading cause of mortality. Early diagnosis is still challenging despite standardised, government‐led screening programs, but is crucial in achieving improved survival rates. Additionally, a deeper understanding of the metastatic potential of breast cancer is critical for developing therapeutic interventions to combat widespread disease. Cutaneous metastasis from underlying breast carcinoma is uncommon as the first manifestation of visceral malignancies and is commonly observed in advanced‐stage malignancies, often associated with poor prognosis, and a prompt, precise tissue diagnosis is mandatory. A high index of suspicion in oncologic patients is required to diagnose these lesions, as they can mimic benign skin manifestations and clinical findings may be subtle and going unnoticed. We report on a case of a 76‐year‐old female patient presenting to our non‐invasive diagnostic outpatient clinic with an unusual cutaneous presentation, as an early sign of locally advanced invasive ductal carcinoma breast cancer recurrence. The aim of our article is to underline the importance of the dermatologist in the multi‐disciplinary oncologic diagnostic process, including non‐invasive imaging evaluation of cutaneous lesions, especially insidious breast carcinomas. Dynamic optical coherence tomography (D‐OCT) is not routinely used due to its cost, therefore lesion's aspect has not been completely described, consequently, the correct evaluation of skin architecture appearance can add important information, especially in cutaneous oncology where it can help in early diagnosis or cancer recurrency. OCT may contribute to the detection of subclinical cutaneous manifestations of cancer or recurrence, in particular, when they are difficult to differentiate clinically from benign lesion. In the case we described, OCT of suspected lesion showed the loss of the DEJ with solid nests and irregular vessels.